Attractiveness as a motive for tanning: results of representative nationwide survey in Germany - Görig, Tatiana; Schneider, Sven; Schilling, Laura; Diehl, Katharina (Photodermatology, photoimmunology & photomedicine, 2020)
Background In previous research, enhancing attractiveness is reported to be an important aspect of tanning motivation. Our aim was to analyze attractiveness as a reason for tanning in a large representative sample in relation to sociodemographic characteristics, perceived risks of ultraviolet radiation (UVR), and exposure to natural and artificial UVR. Methods We analyzed data from 3000 participants (14-45 years) in the German representative National Cancer Aid Monitoring (wave 3). Attractiveness was measured using the General Attractiveness Subscale of the Physical Appearance Reasons for Tanning Scale. Associations were analyzed using chi-square tests and logistic regression analyses. Results Attractiveness played a larger role for participants aged 18-35, those with an immigrant background, medium educational level, and not in a relationship. Significant associations were also identified with a low risk perception of UVR. For sunbathing, the highest OR (9.96, P < .001) was found for high scores on General Attractiveness Subscale, whereas risk perception of UVR was not related to sunbathing in multivariate analyses. For sunbed use, risk perception also only played a minor role as a preventing factor, while higher associations could be identified for age (OR18-25 years = 8.21, P < .001) and attractiveness (OR = 3.55, P < .001). Conclusion Our study showed that people who tan to enhance their attractiveness are more likely to perceive fewer risks of UVR and to show higher UVR exposure behavior and are therefore at greater risk of developing skin cancer. Measures for prevention of UVR-related skin damage should therefore focus more on reducing the positive perception of a tanned appearance instead of only emphasizing the risks of UVR.
First published: 07 November 2019
Gesehen am 26.01.2021